Pengaruh Atribut Produk, Relationship Marketing dan Citra Perusahaan terhadap Loyalitas Deposan PaS iB di PT Panin Dubai Syariah KC Bandung - Aulia Nurul Rohmah; Ida Rapida Djachrab (Masoem University, 2023)
The background of this research is the fluctuating number of PaS iB depositors at PT Bank Panin Dubai Syariah Bandung Branch Office. This study aims to find out how the influence of corporate image, Relationship Marketing and Product Attributes on the loyalty of PaS iB depositors at PT Bank Panin Dubai Syariah Bandung Branch Office. The research object is PaS iB depositors with the type of associative quantitative research and primary data sources. The sample in this study amounted to 58 respondents, with the type of sample incidental sampling, data collection techniques using observation, interviews, questionnaires. The results showed that all independent variables consisting of corporate image, marketing relations, and product attributes had an effect on depositor loyalty either partially or simultaneously.